CD‐1db/db mice: A novel type 2 diabetic mouse model with progressive kidney fibrosis. Issue 6 (3rd July 2020) - Mizunuma, Yuiko; Kanasaki, Keizo; Nitta, Kyoko; Nakamura, Yuka; Ishigaki, Yasuhito; Takagaki, Yuta; Kitada, Munehiro; Li, Shaolan; Liu, Haijie; Li, Jinpeng; Usui, Isao; Aso, Yoshimasa; et al.
Abstract: Aims/Introduction: To establish novel therapies to combat diabetic kidney disease, a human disease‐relevant animal model is essential. However, a type 2 diabetic mouse model presenting progressive kidney fibrosis has not yet been established. Kidneys of streptozotocin‐induced diabetic CD‐1 mice showed severe fibrosis compared with other backgrounds of mice associated with the suppression of antifibrotic peptide N‐acetyl‐seryl‐aspartyl‐lysyl‐proline. The BKS background (BKS db / db ) is often utilized for diabetic kidney disease research; the kidney fibrosis in the BKS db / db phenotype is minimal. Materials and Methods: We generated CD‐1 db / db mice by backcrossing the db gene into the CD‐1 background, and analyzed phenotypic differences compared with BKS db / db and CD‐1 db / m mice. Results: Male CD‐1 db / db mice appeared to have elevated blood glucose levels compared with those of BKS db / db mice. Fasting insulin levels declined in CD‐1 db / db mice. Plasma cystatin C levels tended to be elevated in CD‐1 db / db mice from 16 to 24 weeks‐of‐age. Male CD‐1 db / db mice showed significantly progressive kidney and heart fibrosis from 16 to 24 weeks‐of‐age when compared with that of age‐matched BKS db / db mice. The gene expression profile showed fibrogenic program‐associated genes in male CD‐1 db / db mice. Male CD‐1 db / db mice displayed significantly lower urine antifibrotic peptide N‐acetyl‐seryl‐aspartyl‐lysyl‐proline when compared to that of BKS db / db at 24 weeks‐of‐age. The gene expression of prolyl oligopeptidase, the enzyme essential for antifibrotic peptide N‐acetyl‐seryl‐aspartyl‐lysyl‐proline production from thymosin β4, was significantly lower in the CD‐1 mice. Thymosin β4 levels were also lower in CD‐1 mice. Conclusions: These results suggest that CD‐1 db / db mice are a novel type 2 diabetic mouse model with progressive kidney and heart fibrosis. Abstract : To establish therapies for diabetic kidney disease, a human disease‐relevant animal model is essential. A type 2 diabetic mouse model presenting progressive kidney fibrosis has not yet been established. In this study, we generated CD‐1 db / db mice, which are a novel type 2 diabetic mouse model with a progressive phenotype of diabetic kidney disease including kidney fibrosis.